A rare case of inferior rectus dermoid cyst causing proptosis and optic neuropathy - Mansooreh Jamshidian Tehrani; Arash Ghamar-Shooshtari; Motahhareh Sadeghi (American Journal of Ophthalmology Case Reports)
Purpose: To report a rare case of orbital dermoid cyst, involving the inferior rectus muscle, in a 26-year-old female presenting with proptosis and blurred vision in her right eye. Observations: The unique features of this case are discussed, including the location and contents of the cyst, the surgical approach, and the postoperative outcome. Conclusion and importance: The importance of considering dermoid cysts in the differential diagnosis of an orbital mass involving extraocular muscles and the need for a thorough evaluation to diagnose and manage these rare lesions.